Diversity in the Development of the Neuromuscular System of Nemertean Larvae (Nemertea, Spiralia) - von Döhren, Jörn (Frontiers in Ecology and Evolution, 2021)
In studies on the development of nervous systems and musculature, fluorescent labelling of neuroactive substances and filamentous actin (f-actin) of muscle cells and the subsequent analysis with confocal laser scanning microscopy (CLSM), has led to a broad comparative data set for the majority of the clades of the superphylum Spiralia. However, a number of clades remain understudied, which results in gaps in our knowledge that drastically hamper the formulation of broad-scale hypotheses on the evolutionary developmental biology (EvoDevo) of the structures in question. Regarding comparative data on the development of the peptidergic nervous system and the musculature of species belonging to the spiralian clade Nemertea (ribbon worms), such considerable knowledge gaps are manifest. This paper presents first findings on fluorescent labelling of the FMRFamide-like component of the nervous system and contributes additional data on the muscle development in the presently still underrepresented larvae of palaeo- and hoplonemertean species. Whereas the architecture of the FMRFamide-like nervous system is comparably uniform between the studied representatives, the formation of the musculature differs considerably, exhibiting developmental modes yet undescribed for any spiralian species. The presented results fill a significant gap in the spiralian EvoDevo data set and thus allow for further elaboration of hypotheses on the ancestral pattern of the musculature and a prominent component of the nervous system in Nemertea. However, with respect to the variety observed, it is expected that the true diversity of the developmental pathways is still to be discovered when more detailed data on other nemertean species will be available.